Machine learning-driven investigation of key flavor factors in pale lager beer fermentation samples and their evolution mechanisms during fermentation - Jiang Xie; Ruiyang Yin; Xin Yuan; Bofeng Zhong; Liyun Guo; Yumei Song; Wenjing Tian; Yiyu Chen; Keyi Ling; Dongrui Zhao; Baoguo Sun; Jinyuan Sun; et al. (Food Chemistry, 2026)

Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

Comparative plastid genomics of five Ormosia species (fabaceae): insights into structural variation and morphological homoplasy - Shihong Zhang; Fengcheng Deng; Yixiong Zhao; Jiating Wang; Dipak Khadka; Jieyu Lin; Yuhua Hu; Keyi Fu; Lei Jiang; Mingxuan Zheng; Shi Shi (Plant Systematics and Evolution, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

High-performance and recyclable HKUST-1-derived CuxO/Steel electrode for electrocatalytic dechlorination of trichloroacetic acid - Mengyuan Xu; Yunhua Lv; Keyi Xu; Liqin Zhong; Kunming Wei; Xiaoyan Ma; Su Jiang; Jing Deng; Hanxuan Zeng; Qingsong Li; Stefanos Giannakis; Andrea M. Dietrich (Journal of Cleaner Production, 2026)

One-step treatment of refractory organic pollutants from landfill leachate: alternating magnetic field synergies persulfate activation and in-situ coagulation - Dawei Wang; Yingying Li; Yilan Jiang; Yihan Zhu; Na Huang; Keyi Gao; Jiarong Li; Shijie You (Chemical Engineering Journal, 2026)

Pyrolysis-derived recovered glass fiber-engineered ultrafiltration membrane for dyeing wastewater treatment - Fengzhi Guo; Haolun Wang; Fan Shao; Jinzhi Jiang; Guorui Li; Xinmeng Ma; Haoran Ma; Keyi Li; Lu Gong; Yue Ma; Changtao Yue (Chemical Engineering Journal, 2026)

UVB enhances SLC6A15-mediated phenylalanine transport to promote melanogenesis - Shu Zhou; Yujie Ouyang; Yibo Hu; Xixia Dai; Ling Jiang; Chuhan Fu; Yaqing Wen; Jiangfeng Huang; Keyi Zhang; Jing Chen; Qinghai Zeng (Journal of Photochemistry and Photobiology B: Biology, 2026)

Rapid nucleation and wall-climbing growth of methane hydrate by expanded graphite laminates under static high water-loading conditions - Huizhen Yu; Zixuan Song; Keyi Zhong; Daoyi Chen; Yuanyin Wang; Zihan Yue; Jun Duan; Shuyi Jiang; Mucong Zi (Chemical Engineering Journal, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

Insight into the micro-mechanism of hydrate-based methane storage from active ice - Jun Duan; Keyi Zhong; Shuyi Jiang; Daoyi Chen; Guangjin Chen; Mucong Zi (Fuel, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Metal plate-based promotion on methane hydrate nucleation: Insights into the influence of metal type and surface properties - Yuanyin Wang; Mucong Zi; Shuyi Jiang; Keyi Zhong; Daoyi Chen (Chemical Engineering Journal, 2024)

Regulating the generation of singlet oxygen (1O2) in Advanced oxidation processes by catalyst design for water treatment - Yilan Jiang; Keyi Gao; Tingyue Chen; Yiran Xiong; Yingying Li; Abrham Addisu; Suresh C. Pillai; Dionysios D. Dionysiou; Dawei Wang (Chemical Engineering Journal, 2024)

6:2 Cl-PFESA, a proposed safe alternative for PFOS, diminishes the gemcitabine effectiveness in the treatment of pancreatic cancer - Jiawei Hong; Keyi Du; Weichen Zhang; Junran Chen; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Hanxi Yu; Xiaoyu Weng; Shusen Zheng; Jun Yu; Linping Cao (Journal of Hazardous Materials, 2024)

Interfacial solar evaporation driven Cd removal from contaminated sediments - Keyi Liu; Pan Wu; Yang Ye; Jiashu Jiang; Yuhao Guo; Yuejianshu Li; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

Environment relevant exposure of perfluorooctanoic acid accelerates the growth of hepatocellular carcinoma cells through mammalian target of rapamycin (mTOR) signal pathway - Jiawei Hong; Xiaoyan Wang; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Keyi Du; Diyu Chen; Shusen Zheng; Linping Cao (Environmental Pollution, 2024)

Cotton-based bionic tree-shaped photothermal evaporator for extraction of heavy metals from river sediment - Keyi Liu; Yuejianshu Li; Pan Wu; Yuhao Guo; Yang Ye; Jiashu Jiang; Jiankai Hu; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

Physical activity can influence the relationship between ethylene oxide and risk of kidney stones: A cross-sectional study from the NHANES 2013–2016 - Hua Jiang; Keyi Wang; Heng Zhang; Bin Yang; Weipu Mao; Ming Chen; Shuigen Zhou (Environmental Science and Pollution Research, 2023)

A novel defined risk signature of endoplasmic reticulum stress-related genes for predicting the prognosis and immune infiltration status of ovarian cancer - Jiahang Mo; Shunyi Ruan; Baicai Yang; Yunfeng Jin; Keyi Liu; Xukai Luo; Hua Jiang (Journal of Zhejiang University-SCIENCE B, 2023)

Assimilation of Feng-Yun-3B satellite microwave humidity sounder data over land - Keyi Chen; Niels Bormann; Stephen English; Jiang Zhu (Advances in Atmospheric Sciences, 2018)

Cloning and functional characterization of PjCAO gene involved in chlorophyll b biosynthesis in Pseudosasa japonica cv. Akebonosuji - Keyi Jiang; Mingbing Zhou; Haiyun Yang; Wei Fang (Trees, 2016)

Bio-resolution of glycidyl (o, m, p)-methylphenyl ethers by Bacillus megaterium - Zhengfang Zhang; Yanming Sheng; Keyi Jiang; Zhao Wang; Yuguo Zheng; Qing Zhu (Biotechnology Letters, 2010)